PERANAN PENGELOLA DALAM MENSOSIALISASIKAN USAHA EKONOMI KELURAHAN – SIMPAN PINJAM KEPADA MASYARAKAT KELURAHAN MAHARATU KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Yifani Mirzahani; NURJANAH " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
UEK-SP is a micro finance institution funded by local government and operated in Kelurahan (subsector) of Maharatu has been established for 6 years ago, though some people in Kelurahan Mahararatu still not familiar with the existing of UEK-SP as micro finance institution, which is serves as financial institution in order to assist people for their businees in this area. The management of UEK-SP should responsible for sosializing their existance to the community. The aim of this research to investigate the role of UEK-SP management in sosializing their existance as financial institution and to understand the media used by them in communicating to the community.Quantitative descriptive method was used in this research to see the reality in the field thru observation, interview and documentation. The research was conducted in UEK-SP Maharatu Jaya Kelurahan Maharatu Kecamatan Marpoyan Damai from June 2013 to Nopember 2013. Data was obtained from 10 of informen as source of information. Data was analysed using interactive analysis method with data validation technique dan data tranqualation.The result of this research shows the role of UEK-SP management in sosializing the institution to community thru 3 stages of process, i.e. introduction stage, which is the management of UEK-SP doing sosialization as early stage of sosialization process. At this stage, they introduced to sociaty regarding to UEK-SP as financcial institution and benefit of its existance to community of Kelurahan Maharatu and the differences the institution to cooperative institution. The second stage is persuation, where the management of UEK-SP doing further socialization in order to persuade the people of community of Kelurahan Maharatu to be a member of the institution. At this stage they used printed media, such as booklet to distribute information regarding the institution, and the objectives of the program. The third stage, they used information board which is available at UEK-SP office to inform to the community regarding to activities and financial report of the institution. Besides, the information is also spreading thru spread of mouth.Keyword: Communication, socialization, and role